1998
DOI: 10.1038/bjc.1998.33
|View full text |Cite
|
Sign up to set email alerts
|

Loss of heterozygosity for defined regions on chromosomes 3, 11 and 17 in carcinomas of the uterine cervix

Abstract: Summary Loss of heterozygosity (LOH) frequently occurs in squamous cell carcinomas of the uterine cervix and indicates the probable sites of tumour-suppressor genes that play a role in the development of this tumour. To define the localization of these tumour-suppressor genes, we studied loss of heterozygosity in 64 invasive cervical carcinomas (stage IB and IIA) using the polymerase chain reaction with 24 primers for polymorphic repeats of known chromosomal localization. Chromosomes 3, 11, 13, 16 and 17, in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
53
0
1

Year Published

1998
1998
2002
2002

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 41 publications
12
53
0
1
Order By: Relevance
“…Several recurrent chromosomal aberrations have been described for cervical cancer, detected either by CGH or allelic imbalance (Hampton et al, 1994;Heselmeyer et al, 1996Heselmeyer et al, , 1997Larson et al, 1997;Kersemaekers et al, 1998;Dellas et al, 1999;Kirchhoff et al, 1999). These regions include gain of 3q and losses of 3p, 11q, and 6q as observed in the current series.…”
Section: Discussionsupporting
confidence: 55%
“…Several recurrent chromosomal aberrations have been described for cervical cancer, detected either by CGH or allelic imbalance (Hampton et al, 1994;Heselmeyer et al, 1996Heselmeyer et al, , 1997Larson et al, 1997;Kersemaekers et al, 1998;Dellas et al, 1999;Kirchhoff et al, 1999). These regions include gain of 3q and losses of 3p, 11q, and 6q as observed in the current series.…”
Section: Discussionsupporting
confidence: 55%
“…Furthermore, two of the microsatellite markers showing LOH which were used in the previous studies were mapped to the region of 3p24, which was the smallest Comparative genomic hybridisation in vulvar cancer DG Allen et al region of chromosome loss detected by CGH in the current study. Loss of 3p is also frequently seen in cervical SCC, by CGH and LOH analysis (Heselmeyer et al, 1996(Heselmeyer et al, , 1997bLarson et al, 1997;Wistuba et al, 1997;Kersemaekers et al, 1998;Steenbergen et al, 1998;Dellas et al, 1999;Kirchoff et al, 1999;Allen et al, 2000). Loss of 11q has been documented in cervical and other malignancies not related to HPV infection, including breast, colorectal and ovarian cancers and malignant melanoma (Hampton et al, 1994;Kersemaekers et al, 1998;Allen et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…22 Most of the reports have analyzed LOH in squamous carcinomas and have included in addition few glandular lesions. [7][8][9] Ferguson et al reported a low frequency of deletions in glandular lesions, suggesting that most endocervical adenocarcinomas lack the molecular alterations characteristic of other gynecologic malignancies, including LOH. 6 Larson et al identified LOH in 10 of 13 cell lines derived from squamous cell carcinomas of the cervix, whereas the deletions were not detected in cell lines derived from adenocarcinomas (HeLa and JE6), or adenosquamous carcinoma (XH1).…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8] However, most of these studies have focused on LOH detection in squamous carcinomas and have included only a few cases of adenocarcinomas. A major challenge in identifying allelic deletions in microscopic lesions such as adenocarcinomas or their precursor lesions with a complex pattern of glands admixed with reactive/inflammatory stroma is the need to obtain pure tumor cell populations, because contaminating nonlesional cells can mask the detection of LOH.…”
mentioning
confidence: 99%